The evolution of bone-eating worm diversity in the Upper Cretaceous Chalk Group of the United Kingdom. - Sarah Jamison-Todd; James D Witts; Marc E H Jones; Deborah Tangunan; Kim Chandler; Paul Bown; Richard J Twitchett (PLoS ONE)
The bone-eating worm Osedax is today a member of the highly adapted invertebrate assemblages associated with whale carcasses on the ocean floor. The worm has also been found in a variety of other vertebrates in marine environments. Osedax borings are represented by the trace fossil Osspecus, which has been identified in fossil whales and marine reptiles, with the earliest occurrence in the Albian. In studies of present-day whale bones it has been found that individual species of Osedax create distinct boring morphologies. The diversity of boring geometries therefore provides a proxy for species diversity that can be applied to the fossil record to better understand the diversity, ecology, and evolution of extinct Osedax species. We examined marine reptile fossils from the Upper Cretaceous Chalk Group of the United Kingdom, and found five previously undocumented boring morphologies. These results, coupled with a re-examination of previous records of Osspecus, led to the naming of seven new ichnospecies. Using nannofossil biostratigraphy from the chalk, we constrained the ages of these occurrences and found a high species diversity in the early Late Cretaceous, indicating either a rapid diversification or an earlier origin for Osedax than previously estimated. Furthermore, we recognise five Cretaceous ichnospecies that are also found in the Cenozoic, three of which are also found in present-day whale bones.